Religious social values in the bale beleq celebration of the Jerowaru community East Lombok - Alif Ilman Mansyur; Lailatussakdiah; Budiman (Institute of Computer Science (IOCS), 2023)
The purpose of this study is to determine the social and religious values ??in the celebration of Bale Beleq in the community of Wakan Village, Jerowaru District, East Lombok Regency. This research uses a qualitative research approach with the type of phenomenological research. In this study, researchers collected data using techniques, namely observation, interviews, documentation, data analysis and data validity. Meanwhile, in obtaining data, researchers interviewed related parties, namely stakeholders, and the public. The data analysis used is the miles and humberman model which consists of data reduction activities, data exposure, and drawing conclusions. Based on the results of research on religious socialvalues ??in the celebration of Bale Beleq society Wwill Village, Jerowaru District, East Lombok Regency, which has many values ??contained in it. The social values ??contained in it are 1) the value of mutual cooperation, 2) the value of friendship, 3) the value of togetherness, 4) the value of sharing and, 5) the value of responsibility. Meanwhile, the religious value contained in the celebrationof Bale Beleq is 1) the value of godliness, 2) the value of devotion, 3) the value of tolerance.